Comparison of time-segmented-target teaching and traditional teaching methods for spinal puncture: a randomized trial - Qing, Wenxiang; Su, Han; Cheng, Cancan; Yu, Rili; Hu, Zhonghua; Liu, Xing; Chen, Minghua; Cao, Si; Zhang, Fan (Frontiers in Education, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of a novel “Time-Segmented-Target” (TST) teaching method compared to traditional approaches for spinal puncture training among first-year resident physicians.MethodsWe conducted a randomized trial with 134 participants equally divided into TST and traditional teaching groups. The TST method broke down the spinal puncture procedure into three distinct phases (pre-operative preparation, operation, and postoperative management along with humanistic compassion). Each phase has clear stage teaching objectives and achievement criteria. A reasonable time limit is set for each stage to require students to complete their assigned tasks within the specified timeframe. The traditional method introduce the operational steps from beginning to end, including the goals and achievement criteria for completing each step of the operation. Both groups received 4 h of training. Outcomes were assessed immediately after training and at 2-month follow-up.ResultsThe TST group demonstrated significantly higher competency scores in the pre-operative preparation phase, the operational phase, postoperative management along with humanistic compassion, and total scores (p < 0.01 for each pairwise comparison). Concurrently, the TST group exhibited shorter operational times, and better retention of skills over time (p < 0.01 for each pairwise comparison). Additionally, participants in the TST group reported higher levels of proficiency, willingness, confidence, and satisfaction with teaching (p < 0.01 for each pairwise comparison).ConclusionThe TST teaching method proves significantly more effective than traditional approaches for spinal puncture training, offering improved skill acquisition, retention, and learner satisfaction. These findings suggest TST’s potential value for enhancing procedural skill education.